1999
DOI: 10.1136/adc.80.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Improved prognosis for acquired aplastic anaemia

Abstract: This study compared the prognosis of patients treated for aplastic anaemia at Great Ormond Street Hospital for Children from 1973-88 (group A; n = 38) with a more recent cohort from 1989-96 (group B; n = 37). The two groups were similar in terms of clinical history, age, and severity of aplasia. The main treatment diVerences included the use of androgen treatment in group A (21 of 38 patients) but not in group B, and the addition of cyclosporin A to immunosuppressive treatment for 14 patients in group B. Actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…In younger patients, data comparing the outcomes of HSCT and immunosuppressive therapy in acquired AA had shown better survival rates with HSCT (15–17). However, comparable survival rates between HSCT and immunosuppressive therapy has also been described (13, 18). In the present study, all of the patients were diagnosed to have AA, among whom six of nine were resistant to prior immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In younger patients, data comparing the outcomes of HSCT and immunosuppressive therapy in acquired AA had shown better survival rates with HSCT (15–17). However, comparable survival rates between HSCT and immunosuppressive therapy has also been described (13, 18). In the present study, all of the patients were diagnosed to have AA, among whom six of nine were resistant to prior immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty years ago, a prospective multicentre study reported a 57% chance of survival for severe aplastic anaemia following allogeneic bone marrow transplantation (BMT) from an HLA-identical sibling donor (Camitta et al, 1979), in contrast with recent reports showing that the success of matched sibling donor BMT may now be as high as 90% Pitcher et al, 1999). The 25% survival rate reported in the 1970s for the non-transplanted group (Camitta et al, 1979) contrasts similarly with the 87% probability of 4-year survival reported 20 years later for a cohort of children treated with antithymocyte globulin (ATG) and cyclosporin (Fu È hrer et al, 1998).…”
Section: Review the Modern Management Of Severe Aplastic Anaemiamentioning
confidence: 88%
“…The reasons for the improvement are multifactorial, with probably the greatest differences attributable to the use of cyclosporin in graft-versus-host disease (GVHD) prophylaxis and to improved supportive care, including cotrimoxazole and intravenous immunoglobulin prophylaxis (Bacigalupo, 1999). Certainly, the improved outcome in a single-centre cohort was related to fewer infective deaths than in previous years (Pitcher et al, 1999).…”
Section: Bone Marrow Transplant From An Hla-matched Sibling Donor (Simentioning
confidence: 99%
“…However, our patient showed no spontaneous recovery over a period of 9 months, before intensification of his immunosuppression with ATG. Traditional medical treatment of AA includes a calcineurin inhibitor (typically ciclosporin) with ATG, showing better recovery of bone marrow than with ATG alone (3). Perhaps our patient's problems with adherence to oral medication contributed to the delay in recovery of his AA.…”
Section: Discussionmentioning
confidence: 99%